Implementasi Program Sekolah Adiwiyata Sebagai Upaya Meningkatkan Sikap Peduli Lingkungan Siswa di MAN 2 Pangandaran - Anggun Gunawan (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2025)
Caring for the environment is an attitude or action not to damage nature and help improve natural conditions that have occurred or have been damaged. Protecting nature is a form of environmentally caring behavior that must be instilled from an early age so that the nation's future generations will love nature and the environment around them. School is a formal educational institution that is used to obtain several types of knowledge, starting from religious, social, cultural and environmental knowledge. School is a formal educational institution that is used to obtain several types of knowledge, starting from religious, social, cultural and environmental knowledge. Based on research results, the Adiwiyata Program at MAN 2 Pangandaran is in accordance with the Adiwiyata Guidebook. This is indicated by the environmentally friendly policy component, which has allocated funds amounting to 18% of the total budget for the program Adiwiyata in the framework of the protection and management of the school's environment., the curriculum with an environmental vision is implemented by integrating environmental insight material in subjects both in subjects and extracurricular activities, participatory environmental activities are implemented through environmental action activities both maintained by the school and those organized by outside parties , and managing environmentally friendly facilities.